Late Pleistocene‐Holocene right slip rate and paleoseismology of the Nayband fault, western margin of the Lut block, Iran. Issue 4 (4th April 2014) - Foroutan, M.; Meyer, B.; Sébrier, M.; Nazari, H.; Murray, A. S.; Le Dortz, K.; Shokri, M. A.; Arnold, M.; Aumaître, G.; Bourlès, D.; Keddadouche, K.; Solaymani Azad, S.; et al.
Abstract: The 290 km long Nayband right‐lateral fault cuts across a region seismically quiescent during the last few millennia. Chlorine‐36 and optically stimulated luminescence (OSL) dating of cumulative geomorphic offsets between 9 ± 1 m and 195 ± 15 m with ages from 6.8 ± 0.6 ka to ∼ 100 ka allow deriving a slip rate of 1.8 ± 0.7 mm yr‐1. The paleoseismic record retrieved from the first trench excavated across the fault combined with 18 OSL ages demonstrates the occurrence of at least four large ( Mw ∼ 7) earthquakes during the last 17.4 ± 1.3 ka and two older earthquakes (before ∼ 23 ka and 70 ± 5 ka). Sediments from the last ∼ 7 ka contain evidence of the three younger earthquakes. Penultimate and antepenultimate events occurred between 6.5 ± 0.4 ka and 6.7 ± 0.4 ka within at most 1 ka whereas the most recent earthquake occurred within the last millennium. Such an irregular earthquake occurrence may suggest seismic clustering. Therefore, the imminence of an earthquake along the fault cannot be discarded even if the most recent earthquake occurred within the last 800 years. This event went unnoticed in the historical records demonstrating the incompleteness of the historical seismic catalogs in Central Iran, challenging any assessment of seismic hazard without geologic information. Infrequent large earthquakes typify the slow‐slipping strike‐slip faults slicing Central and Eastern Iran. Also, the slip rates summed from the Iran Plateau up to the Afghan lowlands appear in fairly good agreement with the most recent GPS data. Key Points: Late Pleistocene‐Holocene slip rate of the Nayband fault Paleoseismic history of the Nayband fault Cosmic ray exposure and optically stimulated luminescence dating